Gigabit Optical Wireless: Results and Future Challenges - O'Brien, D; IEEE (2010)
Free-space optical links can achieve rates above 1Gbit/s, but achieving the coverage required for indoor optical wireless systems is challenging. We show results demonstrating bidirectional Gbit Ethernet transmission over 3-4m, and discuss future directions for this work.